The Implications of Price Stabilization for the Short-Term Instability and Long-Term Level of LDC's Export Earnings - Nguyen, D. T. (Quarterly Journal of Economics, 1979)
Journal Article The Implications of Price Stabilization for the Short-Term Instability and Long-Term Level of LDCS' Export Earnings Get access D. T. Nguyen D. T. Nguyen University of Lancaster Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 93, Issue 1, February 1979, Pages 149–154, https://doi.org/10.2307/1882604 Published: 01 February 1979